1983
DOI: 10.1126/science.6836290
|View full text |Cite
|
Sign up to set email alerts
|

Selective Modification of Glutathione Metabolism

Abstract: Glutathione, a tripeptide thiol found in virtually all cells, functions in metabolism, transport, and cellular protection. It participates in the reduction of disulfides and other molecules, and conjugates with compounds of exogenous and endogenous origin. It protects cells against the destructive effects of reactive oxygen intermediates and free radicals. Modifications of glutathione metabolism may be achieved by administration of selective enzyme inhibitors, and also by giving compounds that increase glutath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
556
0
14

Year Published

1995
1995
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,172 publications
(582 citation statements)
references
References 43 publications
12
556
0
14
Order By: Relevance
“…GSH is a tripeptide containing cysteine and AFB 1 easily conjugates with GSH (Janssen et al 1993). GSH is also a major component of red blood cells that plays a central role in the antioxidant defenses of cells (Meister 1983;Ray 1984). Whereas, the significant decrease in the levels of GSH observed in erythrocytes after AFB 1 exposure causes decreased degradation of lipid peroxides leading to their accumulation thus amplifying the toxicity of AFB 1 .…”
Section: Discussionmentioning
confidence: 99%
“…GSH is a tripeptide containing cysteine and AFB 1 easily conjugates with GSH (Janssen et al 1993). GSH is also a major component of red blood cells that plays a central role in the antioxidant defenses of cells (Meister 1983;Ray 1984). Whereas, the significant decrease in the levels of GSH observed in erythrocytes after AFB 1 exposure causes decreased degradation of lipid peroxides leading to their accumulation thus amplifying the toxicity of AFB 1 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that CDDP induced nephrotoxicity can be presented by GSH in renal tissues (Anderson et al, 1990). Furthermore, it has been reported that GSH reacts with ROS and plays a role in the reduction of hydrogen peroxide and organic peroxides (Meister, 1983;Martensson, 1991) and that CDDP is inactivated by direct binding to GSH (Meijer et al, 1990). Ishikawa et al (1993) showed that CDDP reacts with intracellular GSH and that the resulting glutathione-platinum complex is actively exported from leukaemia cells via a GS-X pump.…”
Section: Measurement Of Intracellular Ros Generationmentioning
confidence: 99%
“…Reduced glutathione plays an important role in the protection of cells and tissue structures (23). Its role includes detoxication of xenobiotics, free radicals, peroxides and regulation of immune function.…”
Section: Discussionmentioning
confidence: 99%